2007
DOI: 10.1101/lm.541307
|View full text |Cite
|
Sign up to set email alerts
|

The function of the glutamate–nitric oxide–cGMP pathway in brain in vivo and learning ability decrease in parallel in mature compared with young rats

Abstract: Aging is associated with cognitive impairment, but the underlying mechanisms remain unclear. We have recently reported that the ability of rats to learn a Y-maze conditional discrimination task depends on the function of the glutamate-nitric oxide-cGMP pathway in brain. The aims of the present work were to assess whether the ability of rats to learn this task decreases with age and whether this reduction is associated with a decreased function of the glutamate-nitric oxide-cGMP pathway in brain in vivo, as ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…The neural system underlying emotional memory involves the amygdala [21]. Consistently, in a previous behavioral study, it was shown that aged rats required significantly more trials than young rats to learn the maze task [22]. Aged rats’ memory functions are generally impaired on a wide variety of navigation tasks (e.g., Morris water maze task, T-maze, and Barnes circular platform corridor mazes) [23].…”
Section: Discussionmentioning
confidence: 89%
“…The neural system underlying emotional memory involves the amygdala [21]. Consistently, in a previous behavioral study, it was shown that aged rats required significantly more trials than young rats to learn the maze task [22]. Aged rats’ memory functions are generally impaired on a wide variety of navigation tasks (e.g., Morris water maze task, T-maze, and Barnes circular platform corridor mazes) [23].…”
Section: Discussionmentioning
confidence: 89%
“…26 Reduced function of the pathway in cerebellum is associated with reduced learning of the Y-maze in many pathological situations in rats: developmental exposure to methylmercury or polychlorinated biphenyls, 27,28 rats with chronic hyperammonemia 13 or with minimal hepatic encephalopathy (MHE) due to portacaval shunt 14 or bile duct ligation 29 or in aging of the rats. 30 Also, developmental exposure to PBDE99 enhances the function of the pathway and learning ability. 31 Moreover, in rats with hyperammonemia or MHE, restoring the function of the pathway also restores learning ability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since activation of NMDA receptors leads to an increase of calcium in the post-synaptic neurons, several reports have implicated the role of the glutamate/NO/cGMP pathway in learning and memory [18,37,42]. There is further indication that learning and memory impairment in older animals is a consequence of reduced function of the glutamate/NO/cGMP pathway in the aged brain [47] and probably also alteration in the cholinergic signaling. The increase in PDE expression and activity may lead to more intensive cGMP hydrolysis in the senescent brain.…”
Section: Consequences Of Changes In No/cgmp Pathway On Cognitive Perfmentioning
confidence: 96%